Earnings Losses After Non-employment Increase With Age - Thomas Zwick (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
This paper shows that earnings losses after unemployment increase with age. First, older employees start out with relatively high earnings in comparison to employees without employment interruptions several years before the non-employment spell. This earnings advantage turns into a strong earnings disadvantage shortly before the non-employment spell. Younger unemployed have a relatively stable and small earnings disadvantage before non-employment. Second, while the younger employees quickly enjoy earnings higher than those without employment interruptions after the non-employment spell, earnings for older employees are lower even six years after the unemployment spell. If those with non-employment spells re-enter the labour market at the same employer, the earnings impact is the more positive the younger the employee. This paper uses representative administrative spell data for 1993-2001 that allow us to take into account the precise length of all non-employment spells and calculate the exact dates before and after the spells.
Keywords: J40; J31; C23; 330; Earnings losses; non-employment; age; Verdienstausfall; Arbeitslosigkeit; Erwerbsverlauf; Lebensalter; Deutschland